Neonatal Dandy–Walker syndrome: a case report - Yang, Ying (Frontiers in Pediatrics, 2026)
Dandy–Walker syndrome (DWS) is usually identified prenatally or after hydrocephalus-related symptoms emerge. We report a term male neonate in whom classic DWS was incidentally discovered during admission for purpura and mild tachypnea. Although fetal magnetic resonance imaging (MRI) had suggested vermian agenesis, definitive postnatal brain MRI on day 6 confirmed complete vermian absence, left cerebellar hypoplasia, and a large posterior-fossa cyst communicating with the fourth ventricle. The purpura and respiratory symptoms resolved rapidly with supportive care, and the infant was discharged with full oral feeding at 7 days. This case highlights the need to revisit prenatal imaging when neonates present with seemingly unrelated problems; early postnatal confirmation enables timely family counseling, developmental surveillance, and multidisciplinary follow-up.